Analisis Kesulitan Belajar dalam Memahami Kecemasan Peserta Didik pada Pembelajaran Matematika - wantika, wantika; Nasution, Sri Purwanti (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study is based on the problems that occur in mathematics subjects, where most of the content is abstract, not a few students who find it difficult to learn. This should receive special attention from several parties, such as teachers, school environment, guardians, and the environment. because the subjects of mathematics is one of the mandatory lessons that must be studied all levels of primary and secondary education. This study aims to describe learning difficulties in understanding the anxiety of learners on learning mathematics class X in SMA Muhammadiyah 1 Kotaagung Tanggamus District. In this study population of 37 students with sampling technique in this study using purposive sampling and random class. Data collection in this research is a field data record using documentation, observation, questionnaire, and interview. Learning difficulties can be interpreted as a condition in the learning process characterized by the presence of certain barriers to achieve learning outcomes. In this study more mangacu on the subject of anxiety learners who become obstacles in achieving the objectives of learning .. This research is a type of qualitative research and validity techniques in this study using time triangulation. Based on the results of data analysis and discussion of learning difficulties in understanding students in learning mathematics can be concluded that the factors that affect learning difficulties are physical and physical factors and external factors that are family and environmental factors. Anxiety of learners with low anxiety category is more noticeable and very passionate in mathematics learning compared to the other two categories namely medium anxiety category and high anxiety.